2022
DOI: 10.1186/s12943-022-01496-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of wild type RRAS2, without oncogenic mutations, drives chronic lymphocytic leukemia

Abstract: Background Chronic lymphocytic leukemia (CLL) is the most frequent, and still incurable, form of leukemia in the Western World. It is widely accepted that cancer results from an evolutionary process shaped by the acquisition of driver mutations which confer selective growth advantage to cells that harbor them. Clear examples are missense mutations in classic RAS genes (KRAS, HRAS and NRAS) that underlie the development of approximately 13% of human cancers. Although autonomous B cell antigen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 78 publications
5
24
0
Order By: Relevance
“…These results suggest that other gain-of-function mutations of RRAS2 that are found at low frequency in human tumors and Noonan syndrome patients could also be oncogenic. Consistent with this idea, we have found that R-RAS2 proteins with mutations at residues Gly 23 , Gly 24 , Ala 70 or Gln 72 can transform NIH3T3 cells. Our signaling experiments also indicate that the oncogenic versions of R-RAS2 can potently activate the RAF-ERK and PI3K-AKT pathways in the transformed NIH3T3 cells.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…These results suggest that other gain-of-function mutations of RRAS2 that are found at low frequency in human tumors and Noonan syndrome patients could also be oncogenic. Consistent with this idea, we have found that R-RAS2 proteins with mutations at residues Gly 23 , Gly 24 , Ala 70 or Gln 72 can transform NIH3T3 cells. Our signaling experiments also indicate that the oncogenic versions of R-RAS2 can potently activate the RAF-ERK and PI3K-AKT pathways in the transformed NIH3T3 cells.…”
Section: Discussionsupporting
confidence: 73%
“…1A, B). These data indicate that, like mutations of classical RAS proteins [22], the mutations targeting the Gly 23 , Gly 24 , Ala 70 or Gln 72 residues of R-RAS2 are oncogenic.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Beyond the limited number of tumors bearing oncogenic RRAS2 mutations, it is possible that the WT version of R-RAS2 could play more general roles in human tumors because of gene amplification, upregulated expression, enhanced activity, or presence of mutations in upstream and negative regulatory elements in cancer cells. Genetic evidence in favor of the importance of endogenous R-Ras2 WT in Her2-driven mammary tumorigenesis (Larive et al, 2014), B cell chronic lymphocytic leukemia (Hortal et al, 2022), and Notch1-driven leukemogenesis (this work) is already available for mice. Future studies are needed to better understand the effect of the WT and oncogenic versions of this GTPase in human tumors.…”
Section: Discussionmentioning
confidence: 99%